KAJIAN KOEFISIEN ALIRAN PERMUKAAN DAN EROSI PADA LAHAN HUTAN MONOKULTUR DAN LAHAN PERTANIAN (Studi Kasus di Desa Andongsili, Kecamatan Mojotengah, Kabupaten Wonosobo) - , DEVITA MEISELLA I ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wonosobo regency is a mountainous area with hilly topography. Average air temperature in Wonosobo between 14.3 to 26.5Â° C with an average rainfall every year ranges between 1.713-4.255 mm/year (BPS, 2012). Wonosobo land coverâs in the regionis dominated by moor/garden of 43.70%, wetland 16.28% and Forest 24.72% (BPS, 2012). The diversity of land uses that are not appropriate, especially on steep slopes have a very large contribution to erosion. The research objective to determine the coefficient of runoff and erosion rates on forest land and agricultural land. The research conducted in Andongsili village, Mojotengah Subdistrict, Wonosobo regency. The method used is plot method(small plots) for the measurement of the volume of run off and erossion. Erossion plots measuring 22m x 4 m with different land cover, forest land and agricultural land. Observations were analyzed by t-test on SPSS to know the effect of differences in the coefficient of land run off and erosion. The results showed that the forest land and agricultural land with different land cover obtained 0.022mm/rain events on forest land and 0,012mm/rain events on agricultural land. In the thick of 949.91 mm of rain, the amount of erosion on forest land is 0.006 tons/ha with run off coefficient of 8% while the amount of erosion on agricultural land is 0.008 tons/ha with run off coefficient of 4 %. From the t-test showed runoff 0.031<0.05 so that there is a significant difference between agricultural land and forest land in adsorb rainfall while the value for ttest erosion, showed 0.13>0.05 so that there is no a highly significant difference between forest and agricultural land to produce erosion.